Case Report Penile Fracture With Corpus Cavernosum Rupture Without Urethral Disruption Due to Sexual Intercourse - Pratama, Dio Rancha; Taher, Taufik Rakhman; Jouwena, Davis Roland Gustav (Syntax Corporation Indonesia, 2023)
Objective: We reported a case of penile fracture with unilateral corpus cavernosum rupture that underwent penile exploration and reconstruction measures. Case presentation: We reported a 45-year-old male patient complaining of penile pain, swelling, loss of erectile ability and a